The effect of dynamical fluctuations of hydration structures on the absorption spectra of oxyluciferin anions in an aqueous solution. Issue 15 (3rd April 2017) - Hiyama, Miyabi; Shiga, Motoyuki; Koga, Nobuaki; Sugino, Osamu; Akiyama, Hidefumi; Noguchi, Yoshifumi
Abstract : Photo-absorption spectra of firefly oxyluciferin anions reflecting different hydration structure formed on different isomers, as revealed by ab initio simulations. Abstract : In this study, the effect of hydration on the absorption spectra of oxyluciferin anion isomers in an aqueous solution is investigated for elucidating the influence of characteristic hydration structures. Using a canonical ensemble of hydration structures obtained from first-principles molecular dynamics simulations, the instantaneous absorption spectra of keto-, enol-, and enolate-type aqueous oxyluciferin anions at room temperature are computed from a collection of QM/MM calculations using an explicit solvent. It is demonstrated that the calculations reproduce experimental results concerning spectral shifts and broadening, for which traditional methods based on quantum chemistry and the Franck–Condon approximation fail because of the molecular vibrations of oxyluciferin anions and dynamical fluctuations of their hydration structures. Although the first absorption band associated with the lowest energy excitation corresponds to a π–π* transition for all oxyluciferin anion isomers, the changes in this band upon hydration are different among the isomers. In particular, the bands of enol- and enolate-type of oxyluciferin anions are significantly blue-shifted by hydration, whereas those of the keto-type oxylucifeion anion are shifted relatively less. Thus, the order of the first-peak positions in the aqueous solution changed relative to that in vacuo . We ascribe this to the nature of the oxyluciferin anion being more hydrophobic in the keto form as compared with the enol and enolate isomers.